Letter from Richard Willstätter to Georg Bredig, December 1935 - Willstätter, Richard (1935)
Richard Willstätter (1872-1942), a German organic chemist, inventor of paper chromatography, and 1915 Nobel Prize winner, thanks Georg Bredig (1868-1944) for sending his treatise "Catalysis with Organic Fibers." Willstätter additionally encourages Bredig not to completely give up scientific research despite the rise of the Third Reich and Bredig's forced retirement from the Technical University of Karlsruhe in 1933.
Keywords: Bredig, Georg, 1868-1944; Willstätter, Richard, 1872-1942; Nobel Prize winners; Chemistry, Physical and theoretical